The lady rode bucking horses : - Marvine, Dee (TwoDot, 2016)
The Lady Rode Bucking Horses depicts an era of the American West when capturing renegade horses from the hills above the homestead served as training ground for extraordinary horsemanship. It documents the life of the outstanding girl who outrode them all at stampedes and roundups and the woman she became, her spirit undaunted throughout a life marked with courage and adventure, triumph and heartache.